An experimental investigation of the convective heat transfer augmentation in U-bend double pipe heat exchanger using water-MgO-Cmc fluid - Mustafa M. Gabir; Ibrahim M. Albayati; Mohammad Hatami; Dhirgham Alkhafaji (Scientific Reports, 2024)
Abstract One of the major problems of using nanofluids in heat exchange applications is the forming and deposition of nanoparticles on the inner surface of the heat exchanger. In this paper, Water-Cmc fluid is used as a surfactant for nanoparticles to prevent deposition and congregation. The pressure drops and heat transfer in U-bend double pipe heat exchanger based on water-MgO-Cmc fluid, are examined. Nanoparticles of Magnesium Oxide (MgO) and Carboxymethyl Cellulose (Cmc) are used with pure water as a base fluid. The experimental rig and procedures are designed to facilitate various operational conditions such as flow rate, volume concentration of MgO particles and weight concentration of Cmc particles. Furthermore, convective heat transfer coefficient, heat exchanger effectiveness, pressure drop, friction factor, under different conditions, are measured. The results demonstrate convective heat transfer coefficient of U-bend double pipe heat exchangers is enhanced by 35% for 1 MgO vol.% and 0.2 Cmc wt.% compared to base fluid (Water-Cmc). It is concluded that pressure drops are directly proportion to the increase of MgO nanoparticles at same Cmc concentration by 23% at 0.2 wt.%. Whilst, friction factor of the system is inversely proportion to the increase of volumetric flow rate of water-MgO-Cmc fluid. An increase in MgO nanoparticle concentration increases the friction factor, hence maximum friction factor enhancement by 38% for MgO concentration of 1 vol.%. The effectiveness of heat exchanger is slightly increased by 8% with increase of MgO concentration and flow rate. Finally, thermo-physical characteristics of water-MgO-Cmc fluid at various temperatures, are measured